A Study on Smoke Reduction in Diesel Engines Through Organic Fuel Additives - Gurumani, V.; Senthilvelan, S.; Ramajayam, M.; Ramanathan, A.R. (Asian Journal of Chemistry, 2010)
In addition to industrial applications, diesel engines find wide use in power vehicles due to the economy over gasoline engines. Some earlier studies on diesel engine emission control employing metallic additives are briefly reviewed. Considering the formation of undesirable toxic combustion products by the deposits left by the metallic additives, the authors have in the present study examined, rated and reported the smoke reduction characteristics of eight non-metallic organic compounds (one non-oxygenated and seven oxygenated). The effects of additive concentration and the engine load per cent are outlined. The test results are promissing. However, further studies are required to evolve ideal additives and to better understand the smoke reduction mechanisms.